2022
DOI: 10.3389/fpls.2022.879788
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Optimizes Wheat Quality, Yield, and Nitrogen Acquisition in Low Fertile Calcareous Soil Treated With Organic and Mineral Nitrogen Fertilizers

Abstract: Crop quality and nutrient uptake are considerably influenced by fertilizers inputs and their application rate. Biochar (BC) improves nitrogen uptake and crop productivity. However, its interaction with synthetic and organic fertilizers in calcareous soil is not fully recognized. Therefore, we inspected the role of biochar (0, 10, 20, and 30 t ha–1) in improving N uptake and quality of wheat in a calcareous soil under integrated N management (90, 120, and 150 kg N ha–1) applied each from urea, farmyard manure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…These results are in agreement with [36], who stated that applications of phosphorus optimized the emergence m −2 . Our results are also confirmed by Blair et al [37]. The application of FYM enhanced soil fertility, soil organic matter, and heightened microbial availability [38].…”
Section: Discussionsupporting
confidence: 91%
“…These results are in agreement with [36], who stated that applications of phosphorus optimized the emergence m −2 . Our results are also confirmed by Blair et al [37]. The application of FYM enhanced soil fertility, soil organic matter, and heightened microbial availability [38].…”
Section: Discussionsupporting
confidence: 91%
“…Biochar is not a simple carbon material with uniform physical and chemical properties [10]. Therefore, considering the source of biochar, synthesis conditions, type of soil, and even the type of the crop are essential factors that should be collectively considered for achieving better sustainable agricultural production without posing undesirable physical or biological alternations to utilized agroecosystems [2,11]. Biochar effect is soil type-dependent; for example, for decreasing sandy soil bulk density, at least 1% of biochar addition is required, whereas it was at least 5% for sand-loam soil [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar effect is soil type-dependent; for example, for decreasing sandy soil bulk density, at least 1% of biochar addition is required, whereas it was at least 5% for sand-loam soil [12,13]. Indeed, it is frequently reported that the application of biochar to soil for ameliorating its properties and enhancing crop productivity is more successful with well-weathered soils (degraded), low fertility soils, and acidic soils, than with fertile healthy soils [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with those reported by Ali at al. (2015) and Khan et al, (2022) who observed improve in wheat grain protein content in response to biochar addition.…”
Section: Traitsmentioning
confidence: 95%